Combination of stem cells from deciduous teeth and electroacupuncture for therapy in dogs with chronic spinal cord injury: A pilot study - Prado, Cesar; Fratini, Paula; Schiavo Matias, Gustavo de Sa; Bocabello, Renato Z.; Monteiro, Juliana; Santos, Cello J. dos; Joaquim, Jean G. F.; Giglio, Robson F.; Possebon, Fabio S. [UNESP]; Sakata, Stella H.; Miglino, Maria A. (Elsevier B.V., 2019)
Spinal cord injury (SCI) is a serious condition that causes profound economic and emotional impact in human patients and companion animal owners. It has been shown that the neurogenic effects of the stem cells are enhanced when combined with electroacupuncture (EA) in rodent models of SCI. To determine the safety and feasibility of combining transplantation of allogenic stem cells derived from canine exfoliated deciduous teeth (SCED) and EA in dogs with chronic spinal cord injury a canine pilot clinical study was conducted. A total of 16 individuals ranging from 5 to 11 years at 3 to 18 months of injury were investigated and randomly assigned to 4 experimental groups (SCED, EA, SCED + EA, control). Mild neurological and functional improvements were seen in all 4 groups. There was no clinical progression or mortality of the cases occurred in a follow up of 7 months after procedure. The study shows that SCED transplantation and electroacupuncture were feasible, safe and potentially beneficial. However Long-term patient monitoring is necessary to rule out any delayed side effects and assess any further improvements.
Keywords: Intervertebral disc herniation; Intervertebral disc disease; Stem cells from exfoliated human dental pulp; Cell therapy; Electroacupuncture